Analisis Pengaruh Kemampuan Kerja, Insentif, Dan Disiplin Kerja Terhadap Produktivitas Kerja Di PT. Nayati Indonesia Kota Semarang - Aji Sulistiyo; Wachid Fuady R (Jurnal Ekonomi Manajemen Akuntansi, 2021)
This study aims to determine the effect of work ability, incentives, and work discipline on work productivity at PT. Nayati Indonesia Semarang. The population in this study were all production employees at PT. Nayati Indonesia Semarang. The sample used was 82 respondents with simple random sampling technique. The data used is primary data, with data collection techniques using interviews and questionnaires, and data analysis used is multiple linear regression analysis. The results showed that the value of the coefficient of determination was 0.685, meaning that the variables of work ability, incentives, and work discipline could explain the variation in work productivity variables of 68.5%. The results of hypothesis testing with the statistical t test show that (1) Work ability has a positive and significant effect on work productivity, (2) Incentives have a positive and significant effect on work productivity, and (3) Work discipline has a positive and significant effect on work productivity.